DEVELOPMENT OF SMART VILLAGES AS A FACTOR FOR RURAL DIGITAL TRANSFORMATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The concept of digital transformation, which refers to the use of strategically managed digital technologies to achieve various economic and social goals, is increasingly visible in various development programs of the European Union and Latvia. The aim of the digital transformation is to create a society, economy and public administration that purposefully uses the existing and creates new opportunities of digital technologies, improving the quality of life for every individual and society as well, raising the competitiveness of the country and economy. The National Development Plan of Latvia for 2021-2027 also identifies the further development of digitalization as a pervasive element for all sectors, especially in such areas as innovation and science, education, health care, inclusive society and labor market, infrastructure, regional development, security, as well as also environment and energy. In order to do this, the “Digital Transformation Guidelines for 2021-2027” have been developed, which set out the goals, directions and tasks of the digital transformation policy. One of the basic conditions for digital transformation is a digitally skilled society. To develop the rural environment, including through digital solutions, an initiative supported by the European Commission – ‘Smart Villages’, has been in place since 2016. It is a relatively new concept in EU policy-making and includes a vision for the future of rural areas. ‘Smart’, in the sense of this concept, means the development of new forms of cooperation – between farmers and other entrepreneurs in rural areas, between municipalities, the private and public sectors, and cooperation takes place from the bottom up and from the top down. Smart village strategies can ensure that the digital needs, priorities and capabilities of the rural population are addressed at local level and can help to link these core activities to national and regional digital strategies. The aim of the research is to study the development opportunities of smart villages and their potential in the process of digital transformation of the rural environment. The study carried out an analysis of the rural and regional policies, as well as digital transformation strategic documents. The article also examines examples of the use of digital solutions in smart villages in European countries. The study concludes that the introduction of the concept of smart villages is an effective tool for digital transformation in rural areas, both processes have a common goal and tasks, the most important of which is to take actions to prevent working-age persons from leaving local areas, moving to the capital city Riga or leaving Latvia.